KARAKTERISTIK DIREKSIONAL KOPLER MENGGUNAKAN TEORI MODA TERGANDENG DAN METHOD OF LINES - Syahriar, ary; Adam, Helmi (Badan Pengkajian dan Penerapan Teknologi, 2006)
Single mode directional couplers are key components in many optical communication and sensor applications, including optical power splitting, optical filtering, optical reflecting, wavelength multiplexing/demultiplexing, and optical polarisation splitting. The general basic principle in most directional coupler is that under appropriate conditions light transfer can occur between the two adjacent fiber cores via a mechanism called evanescent wave coupling. When the two cores are put closely together the evanescent field travelling from the throughput fiber reaches the coupled waveguide and excite a mode in it. In this paper we use two approaches in analyzing the properties of directional couplers, namely the coupled mode thery and the method of lines. it is found that the two methods agree very well.